Effect of bacillus thuringiensis on the biological parameters and phytophagy of podisus nigrispinus (hemiptera: pentatomidae) - Dibelli, Wanderlei [UNESP]; De Bortoli, Sergio Antonio [UNESP]; Linhares Volpe, Haroldo Xavier [UNESP]; Vacari, Alessandra Marieli [UNESP]; Magalhaes, Gustavo Oliveira de [UNESP]; Duarte, Rogerio Teixeira [UNESP]; Polanczyk, Ricardo Antonio [UNESP] (E Schweizerbart'sche Verlagsbuchhandlung, 2013)
The effect of Bacillus thuringiensis Berliner 1911 var aizawai strain GC-91 (Bta) on the biological parameters and phytophagy of Podisus nigrispinus (Dallas 1851) (Hemiptera: Pentatomidae) were evaluated using the follow treatments: a) provision of deionized water and prey Plutella xylostella (Linnaeus 1758) (Lepidoptera: Plutellidae); b) provision of only a solution containing Bta; and c) provision of prey and the solution containing Bta. To evaluate the phytophagy of the predator, leaves of Brassica oleraceae var acephala Linnaeus cv Manteiga da Georgia were provided and replaced every two days, and subsequently stained by immersion in 1% acid fuchsin. Staining enabled the visualization of the feeding sheath, which allowed for the quantification of punctures inflicted by P nigrispinus. The phytophagy, reproductive capacity and biological cycle in P nigrispinus were negatively affected by the presence of Bta; however, its predatory capacity was not altered.
Keywords: Plutella xylostella (Linnaeus 1758); Podisus nigrispinus (Dallas 1851); phytophagy; Biological control; Predation; Entomopathogen